ENGRAVING ON THE NET: DEMOCRATIZATION, CONTEMPORARY PRACTICES AND DISSEMINATION OF THE ART OF ENGRAVING - Alves, Daniel Lucena da Hora (Seven Editora, 2025)
The article addresses the extension project "Engraving on the Network", carried out by the Visual Arts course at the Federal University of Paraíba (UFPB), as an interdisciplinary proposal that articulates teaching, research and extension to democratize access to the artistic practice of engraving. Based on hybrid methodologies, the project promotes workshops and activities that resignify traditional engraving techniques by integrating contemporary and digital processes, consolidating itself as a space for artistic experimentation and social transformation. The results reveal the potential of engraving as a relational and critical language, capable of generating an impact both in academic training and in the communities served, evidencing the relevance of university extension in strengthening the bond between the university and society. DOI: https://doi.org/10.56238/sevened2024.037-212